Rapid synthesis of potassium sodium niobate (K 1/2Na 1/ 2NbO3) lead-free piezoelectric powder using the combustion method - Chaiyo, Nopsiri; Muanghlua, Rangson; Wongprasert, Yothin; Seeharaj, Panpailin; Vittayakorn, Naratip (My University, 2013)
Potassium sodium niobate (K1/2Na1/2NbO3) powder was synthesized successfully by the combustion synthesis. The raw materials of KNO3, NaNO3 and Nb2O5 were used with glycine as fuel. The thermal behaviour of the precursor was determined using thermo gravimetric analysis (TGA) and derivative thermo gravimetric (DTG) analysis. The conditions for preparing perovskite phase formation, influence of the fuel-to-oxidizer molar ratio, and crystal structure were characterized by the X-ray diffraction technique (XRD) and Fourier transform infrared (FTIR) spectroscopy. The morphology and particle size were investigated through a scanning electron microscope (SEM). © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: combustion synthesis; Lead-free piezoelectric; potassium sodium niobate